Carving out the end of the world or (superconformal bootstrap in six dimensions) - Chi-Ming Chang; Ying-Hsuan Lin (Journal of High Energy Physics, 2017)
Abstract We bootstrap N = 1 0 $$ \mathcal{N}=\left(1,0\right) $$ superconformal field theories in six dimensions, by analyzing the four-point function of flavor current multiplets. Assuming E 8 flavor group, we present universal bounds on the central charge C T and the flavor central charge C J . Based on the numerical data, we conjecture that the rank-one E-string theory saturates the universal lower bound on C J , and numerically determine the spectrum of long multiplets in the rank-one E-string theory. We comment on the possibility of solving the higher-rank E-string theories by bootstrap and thereby probing M-theory on AdS 7 × S 4 / ℤ 2 $$ AdS_7× S^4/{\mathrm{\mathbb{Z}}}_2 $$ .